PERAN DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MENINGKATKAN KUALITAS TENAGA KERJA DI KABUPATEN SUMBAWA - Sutama, I Nyoman; Rahim, Abdul; Hasanah, Aulyatun (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to know the role of the Manpower and Transmigration Office in improving the quality of workforce in Sumbawa District. The type of this study was descriptive study which aims to describe the role of the Manpower and Transmigration Office in improving the quality of workforce in Sumbawa District. The type of data used was qualitative data in the form of research informants' perceptions regarding research objects collected directly by researchers from the original source, namely research informants using interview techniques. The informants in this study consist of key informants and main informants. Data analysis was carried out using qualitative analysis techniques proposed by Miles and Huberman, including data reduction, data display, and drawing conclusions/verification. The results of this study indicate that the Manpower and Transmigration Office had an important role in improving the quality of the workforce in Sumbawa District through various programs and activities. These programs and activities include competency-based education and training, internships, and coaching of Private Job Training Institutions. Through these programs and activities, it can provide adequate knowledge and competency for the workforce as provisions before entering the workforce, thereby increasing greater opportunities for the workforce to be able to participate in the workforce. Thus, the Manpower and Transmigration Office of Sumbawa District had played an important role in creating a skilled, productive and independent workforce that is in accordance with the needs and demands of the current and future workforce.